2013
DOI: 10.1136/jnnp-2013-305019
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis on the natural history of incidental small paraclinoid unruptured aneurysm

Abstract: Although incidental small paraclinoid UIAs have a relatively lower rupture and growth risk, patients with high-risk factors, including aneurysm ≥4 mm, HTN, arterial branch-related aneurysms, and multiple aneurysms must be monitored closely. The limitation of the retrospective nature of this study should be taken into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…Twenty-one studies reported risk factors for aneurysm growth, including 3954 patients with 4990 aneurysms with 11,000 patient-years and 13,294 aneurysm-years of follow-up. 9,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Eleven of these studies reported the rupture rate of growing aneurysms. Mean patient follow-up was 4.9 years, and median was 3.2 years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Twenty-one studies reported risk factors for aneurysm growth, including 3954 patients with 4990 aneurysms with 11,000 patient-years and 13,294 aneurysm-years of follow-up. 9,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Eleven of these studies reported the rupture rate of growing aneurysms. Mean patient follow-up was 4.9 years, and median was 3.2 years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Transitional paraclinoid aneurysms-i.e., aneurysms arising from the clinoid-ophthalmic segment of the ICA and straddling across the DDR with potential risks of subarachnoid hemorrhage-necessitate treatment. 8 Defining the transition of paraclinoid aneurysm from the extradural to intradural spaces can be difficult. Imaging studies that analyze the traditional anatomical landmarks, including the ACP and the origin of the OphA on DSA, 20,22 have been used.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,10,17,18,25 It is important to differentiate the exact location of the paraclinoid aneurysm, whether intradural or not, when considering treatment options. The distal dural ring (DDR) is the anatomical boundary between the intra-and extradural segments of the internal carotid artery (ICA) in the paraclinoid region.…”
mentioning
confidence: 99%
“…Good results have been published in the literature with the use of FDS, with occlusion rates of up to 90% and complications lower than 5%, however surgical clipping remains an acceptable option to achieve high occlusion rates with average complications 1,2,3,4,5,18,19,20 . The purpose of this study is to expose our surgical results and match them with those of the FDS era.…”
mentioning
confidence: 91%